Sistem Pendukung Keputusan Pemilihan Supplier Telur di Toko Kelontong Menggunakan Metode AHP - Lubis, Birrham Efendi; Fadillah, Muhammad Zidan; Mujizat, Hafidza Dafariz; Danuyasa, Abiyanfaras; Anshor, Abdul Halim (Jurnal Kridatama Sains dan Teknologi, 2024)
Choosing the right supplier is crucial for a grocery store business, especially to ensure product quality, delivery speed, and cost efficiency. The purpose of this study is to determine the best egg supplier for Mrs. Tuti. Mrs. Tuti Suryati's grocery store applies the Analytical Hierarchy Process (AHP) method which is designed to help the complex decision-making process based on key criteria such as price, egg quality, and delivery reliability. The AHP method simplifies evaluation by separating each criterion based on its importance through pairwise comparisons, so that the final order of each supplier can be arranged objectively. Research information was obtained from two respondents, namely the store owner and an employee who manages procurement. Interviews provided information on the three main criteria and supplier choices, while literature served as secondary data to strengthen the criteria analysis. Based on the AHP calculation, Supplier A has the highest average weight of 0.4377, so it is recommended as the best option when compared to Supplier B and Supplier C. This recommendation is based on a systematic and consistent evaluation of the criteria, which helps Mrs. Tuti Suryati in determining the supplier that suits her business needs and the desires of her store's customers